(untitled) (Asian-Australasian Journal of Food Safety and Security, 2022)
Bacterial blight (BB) caused by Xanthomonas oryzae pv. oryzae is a destructive disease of rice causing significant yield losses. Surveys were conducted to know the influence of weather parameters on epidemic development of BB in the thirty agroecological zones of Bangladesh. The maximum (55.11%) BB incidence and severity were recorded in Mymensingh division (AEZs 8 and 9) while the minimum (3.25%) incidence was observed in Barishal division (AEZ 13) in both rainfed and irrigated seasons. In rainfed conditions, the maximum BB incidence and severity were recorded in hybrid varieties Aloron from Netrokona (AEZ 9) and the minimum incidence was observed in the local variety Sughondi from Jalhokhati (AEZ 13). On the other hand, in irrigated conditions, the highest BB incidence was recorded in the hybrid variety Hera-2 from Netrokona (AEZ 9) and the lowest incidence was observed in the local variety from Hobiganj (AEZ 20, 21, 22). Swarna, Puja, BRRIdhan28, BRRIdhan29, and BRRIdhan49 showed intermediate levels of infection, while hybrid Hera-2, Arize TejGold, Partex, Agrodhan, Aloron, ACI-2, and Dhani Gold showed higher level of infection (susceptibility) to BB. The data analysis on BB incidence with the weather parameters of rice growing seasons from 2015 to 2017 revealed that the rainfall distribution varied greatly within rice growing seasons over the years. The results indicated that weather parameters, viz. temperature (25-34°C), relative humidity (70-84%), and rainfall (>200mm), largely affected the prevalence, incidence and severity of BB. The correlation studies revealed that among the climate variables, minimum temperature exhibits a negative correlation. However, rainfall, maximum temperature, morning relative humidity and evening relative humidity were found positively correlated, while wind velocity imparted a significant positive correlation with BB infection. The regional outbreak of BB indicated a considerable yield loss of rice and give rise a threat for food security of the country. Asian Australas. J. Food Saf. Secur. 2022, 6 (1), 35-47